EMPOWERMENT MODEL OF WOMEN FARMER GROUPS IN IMPROVING THE COMMUNITY ECONOMY IN KLATEN REGENCY - Rozikin, Mochammad; Suryono, Agus; Putra, Endry; Novita, Asti Amelia (Erudio Journal of Educational Innovation, 2024)
The conceptual construction of the empowerment process places several stages of empowerment which are now influenced by the concept of social capital and the perspective of local economic development. This has generated interest in research that focuses on the steps to empower local communities, as well as the supporting and inhibiting factors of the empowerment process. This research was conducted at the Women's Farmer Group (KWT) Mekar Indah, Balerante Village, Klaten Regency, and used a qualitative approach combined with a fishbone diagram to produce a community empowerment model construction in local economic development. This study shows that the empowerment steps are carried out in 3 (three) stages, namely enabling by forming women's farmer groups. Empowering is done by empowering farmer groups to be able to meet their food needs, and increase financial income. Meanwhile, protecting is carried out with government support, compliance with common rules and social norms, as well as maintaining good relations within the network with members and with external parties. The empowerment process is also supported by the existence of social capital that is maintained together. The empowerment process also produces development potential that leads to the achievement of local economic development that utilizes natural resources and product commodities, as well as the support of the context of the institutional system and good governance.